Relationship among Serum hsp65 Antibodies, Neopterin, Autoantibodies and Atherosclerosis - Xu Qingbo (Pteridines, 1994)
A statistical reinvestigation was performed on data from two separate earlier studies, investigating heatshock protein 65 and neopterin in the same population of subjects examined for the presence of carotid atherosclerosis. Both heat-shock protein 65 and neopterin concentrations are significantly correlated with atherosclerosis, but the correlation between both biochemical analytes is low albeit significant. Neopterin, but not heat-shock protein 65 concentrations were shown to be significantly higher in women with presence of antinuclear antibodies, particularly in women older than 65 years of age. This finding seems to explain earlier observations of raised neopterin concentrations in such older women, irrespective of the presence or absence of atherosclerosis.